ANALISIS AKAR PENYEBAB MASALAH DALAM MENINGKATKAN OVERALL EQUIPMENT EFFECTIVENESS (OEE) MESIN STRIPPING HIPACK III DAN UNIMACH DI PT PFI - Firman Alamsyah (Universitas Mercu Buana, 2015)
Abstract. Overall Equipment Efectiveness (OEE) is a calculation method used inTotal Productive Maintenance (TPM) to maximize the effectiveness of machinesin industrial facilities. OEE value is determined by availability rate, performancerate and quality rate. Low OEE of the Hipack III and UNIMACH strippingmachine at PT Promedrahardjo Pharmaceutical industry identified the loweffectiveness of the machine. The aim of research is to improve the effectivenessof the machine by increasing its OEE value. The analytical method used is theanalysis of six big losses, fishbone diagrams, and pareto diagram. The results ofthe research show that the six big losses dominant factors in the machine aredowntime and speedlosses. The focused improvements on minimazing it factorsincrease the OEE machines.Keywords: Total Productive Maintenance, Overall Equipment Effectiveness,Analisis Six Big Losses, Fishbone Diagram, Pareto